The Concept of Ulil Amri in Al-Sunnah: Theological and Social Implications in Nationhood - Dadang Syaripudin; Ah. Fathonih; Nanang Naisabur; Ramin Ramin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research aims to examine the concept of Ulil Amri as described in the Quran and Sunnah, and how obedience to Ulil Amri is applied in the context of nationhood, particularly within modern political systems. The research uses a qualitative method with a descriptive-analytical approach, focusing on the interpretation of religious texts and related literature. Primary data sources include the Quran, Hadith, and the commentaries of classical and contemporary scholars, such as Ibn Qayyim, Al-Tabari, and Yusuf Al-Qaradawi. The main findings indicate that obedience to Ulil Amri has clear limitations, particularly when leaders do not govern in accordance with Islamic law. Additionally, the concept of Ulil Amri faces challenges in the modern era, especially in countries that do not fully implement Sharia law. The role of scholars in ensuring that leaders' policies remain aligned with Islamic values has become increasingly significant. The research concludes that obedience to Ulil Amri remains relevant; however, Muslims must balance this obedience with constructive criticism through the principle of Amar Ma’ruf Nahi Munkar when necessary. Consequently, this study suggests that the concept of Ulil Amri in Islam can be dynamically applied within the framework of modern governance.